The migration of fear: An analysis of migration choices of Syrian refugees - Balcilar, Mehmet; Nugent, Jeffrey B. (Elsevier Science Inc, 2019)
The current literature on forced migration offers only limited knowledge of how each of the different consequences of war, such as damage to property and casualties to family members, and the services provided to the refugees in the host country, affect the difficult choices that refugees subsequently must make as to when and where to migrate from their location as refugees. This paper contributes to that literature by studying the effects of armed violence in Syria on the intentions of Syrian refugees in Turkey to return to Syria, stay in Turkey or move on to Europe and elsewhere. The study is based on three waves of a survey of Syrian refugees in Turkey. Special attention is given to the impacts of war (loss of home, property damage and casualties) and the duration of stay and quality of services received as refugees in Turkey, as well the individual characteristics of the refugees (e.g., gender, age, education, and income). The results show that (1) the longer and greater the level of violence in the country of origin, and the longer the time spent outside of Syria, the lower the likelihood that the refugee will want to return to Syria; (2) the longer the time the refugee has spent in Turkey, the higher is the probability of permanent settlement in another European country; and (3) the more and higher quality of services provided to the refugees, the more likely they are to remain in Turkey. The results offer insights into the design of international policy for dealing with the violence and the handling of refugees. (C) 2018 Board of Trustees of the University of Illinois. Published by Elsevier Inc. All rights reserved.
Keywords: Refugees; Forced migration; Labor market; Employment; Immigration; Logit; Model; Civil war; Syria; Turkey